A study on the information transmission of Islamic stock market in Middle East Countries (Kuwait, Qatar, United Arab Emirates) / Siti Marsufah Mohamed Ali - Mohamed Ali, Siti Marsufah (2010)
There are many research have been conduct in order to investigate the relationship between the conventional stock market of the developed and emerging countries in literature such as Abraham and Seyyed (2006), Babaker (2004), Bekaert and Harvey (1995), Hammoudeh and Choi (2004). The knowledge has been expended by Rahim, Ahmad and Ahmad (2009) by exploring the international market interdependence among Islamic stock market in South Asia. This study tries to extend the body of knowledge by analyzing the information transfer between Shariah stock market in Middle East by using three Shariah stock market which are Kuwait, Qatar and United Arab Emirates. The Vector Autoregression (VAR) model was applied on the daily price stock index from March 2007 until December 2009. The result shows that there is unidirectional price relationship run from UAE Shariah stock market, Qatar Shariah stock market and Kuwait Shariah stock market. However, the finding exposed that there is bidirectional relationship between Kuwait Shariah stock market and Qatar Shariah stock market. Beside that, the result from this study has some potential to be used by the market analyst for predicting country market movement and also useful to regulators of stock markets in regulating policies to control the price relationship between those markets.